2020
DOI: 10.1016/j.eclinm.2020.100378
|View full text |Cite
|
Sign up to set email alerts
|

Risk of repetition and subsequent self-harm following presentation to hospital with suicidal ideation: A longitudinal registry study

Abstract: Background: Few studies have focused on those who present to hospital with suicidal thoughts (suicidal ideation). The aim of this study was to establish the risk of repeat presentation to hospital following suicidal ideation and to identify factors which were associated with further ideation or subsequent self-harm. Methods: Data were obtained from the Northern Ireland Registry of Self-harm. Risk of repeat presentation following hospital-presenting ideation was analysed using Kaplan Meier analyses, specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Our findings, therefore, are consistent with and complement those from studies that have investigated the association between these phenomena over time (Mars et al, 2019 ; Neeleman et al, 2004 ; Ribeiro et al, 2016 ). Based on these data and recognizing that (a) suicidal ideation is one of the strongest predictors of psychiatric hospitalization and death by suicide (Klonsky et al, 2013 ), and (b) that individuals who present to hospital with suicidal ideation are at risk of repeat presentation and future self‐harm (Griffin, Kavalidou, Bonner, O’Hagan, & Corcoran 2020 ), early interventions that target and treat suicidal ideation are likely to be beneficial in preventing suicide‐related behaviors. Existing psychotherapies such as Dialectical Behavior Therapy (Geddes et al, 2013 ) and Cognitive‐Behavior Therapy (Tarrier et al, 2008 ) have been shown to be effective in reducing suicidal thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, therefore, are consistent with and complement those from studies that have investigated the association between these phenomena over time (Mars et al, 2019 ; Neeleman et al, 2004 ; Ribeiro et al, 2016 ). Based on these data and recognizing that (a) suicidal ideation is one of the strongest predictors of psychiatric hospitalization and death by suicide (Klonsky et al, 2013 ), and (b) that individuals who present to hospital with suicidal ideation are at risk of repeat presentation and future self‐harm (Griffin, Kavalidou, Bonner, O’Hagan, & Corcoran 2020 ), early interventions that target and treat suicidal ideation are likely to be beneficial in preventing suicide‐related behaviors. Existing psychotherapies such as Dialectical Behavior Therapy (Geddes et al, 2013 ) and Cognitive‐Behavior Therapy (Tarrier et al, 2008 ) have been shown to be effective in reducing suicidal thoughts.…”
Section: Discussionmentioning
confidence: 99%
“…Considerably more research on suicide is needed in many areas so it would be impossible to identify all of the places where we should focus our attention. Given this, I conclude this commentary by highlighting two (of potentially many) themes for future research that build off of work done by Griffin et al [1] and others who have studied suicide thinking. First, it is important to explore suicidal thinking in settings beyond the hospital.…”
mentioning
confidence: 90%
“…In this issue, Griffin and colleagues [1] present data on repeat hospital presentations among those who visit the hospital due to suicidal thinking (also called suicidal ideation). They found that about 4 in 10 people who visited the hospital once for suicidal thinking did so again within five years.…”
mentioning
confidence: 99%
“…Overall, SI represents the most important and direct risk factor for suicide, whereas the prevalence of DSH among patients who died by suicide was estimated around 58%, so DSH could be considered as a subthreshold suicidal symptom (Klonsky and May, 2010; Griffin et al ., 2020). It is estimated that 33.6% of individuals experiencing suicidal thoughts would subsequently develop a suicidal plan, and 56% of those with a plan would attempt suicide (Littlewood et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%